Application of UV-synthesized anion exchange membranes to improve nickel removal through galvanic deposition process. Issue 2 (1st February 2023) - Delsouz Chahardeh, Masoud; Bozorg, Ali
Abstract: Nickel removal from sodium chloride solution has been studied in an electrogenerative cell and the effect of synthesized anion exchange membranes on the galvanic deposition process was investigated. As shown, although in the absence of the membranes, the highest electrical potential of 0.985 volts was achieved, nickel removal efficiency was the lowest. On the other hand, electrical potential as high as 0.976 volts was achieved from the galvanic cell when the UV-curable membrane was employed between the two galvanic cell compartments. Using such electrogenerative process facilitated by the advanced anion exchange membranes, 37.2% of nickel ions were spontaneously removed from a solution of 0.04 M NaCl containing 100 ppm initial nickel ions. Furthermore, the introduced UV-synthesized membranes revealed to have a rigid polymer network and sufficient mechanical and thermal stability with tensile strength of 26.9 MPa and degradation temperature of 415 °C. Graphical Abstract: UF0001